SmartMedicist: a context-aware system for recommending an alternative medicine. Issue 2 (4th June 2018) - Swain, Sujata; Niyogi, Rajdeep
Abstract : Purpose: This study aims to discuss a context-aware system, SmartMedicist, which can recommend an alternative medicine from a set of available medicines present at a patient's home for an unavailable medicine. The system is applied to the chronic disease patients only. The system requires only a smartphone, and provides a reminder to the patient to take medicine at appropriate times and to procure medicines from drug store. The system discusses the output method for the physically challenged patient. Although there are existing systems that can remind a patient for taking medicines, the authors are not aware of any such system that has the capability to recommend an alternative medicine for the prescribed medicine. Design/methodology/approach: The study developed a pharmacology knowledge base that consists of a representation of a set of diseases, according to family, type and medicines, in a k-ary tree. An alternative medicine is recommended based on the set of available medicines and knowledge base. Findings: We considered four diseases: Hypertension, Gastritis, Alzheimer's disease, and Parkinson; and performed several experiments for each disease for the different number of available medicines. The execution time to find an alternative medicine (if any) in each case is around four seconds. Originality/value: The proposed system is cost effective and affordable for most families in India. Although the proposed system is not a substitute of a doctor, this system will enhance the safety golden period for a patient to consult a doctor in the emergency exhaustion of the prescribed medicines.